Real‐world experience of adjuvant immunotherapy for stages III–IV melanoma: A monocentric observational study - Manon Blaise; Eric Fontas; Barbara Seitz‐Polski; Laura Troin; Alexandra Picard; Perrine Rousset; Elodie Long‐Mira; Micheline Razzouk‐Cadet; Madleen Chassang; Thierry Passeron; Henri Montaudié (JEADV Clinical Practice)
Abstract Background Adjuvant immunotherapy (AIO) improved recurrence‐free survival (RFS) in patients with resected stages III–IV melanoma. Real‐world data, especially in elderly patients, as well as optimal management of patients who relpases, are still limited. Objectives To evaluate real‐world outcomes of AIO in a cohort of stages III–IV melanoma patients. Methods We conducted a monocentric, retrospective, observational study that included patients treated with AIO (nivolumab or pembrolizumab) for stages III/IV melanoma. The primary endpoint was RFS. Subgroup analyses were performed. Results A total of 76 patients were included, with a mean age of 64.6 years (51.3% and 31.6 age ≥65 and ≥75 years, respectively). Majority received nivolumab (67.1%). Median follow‐up period was 26.4 months (interquartile range, 17.9–35.1 months). The RFS rates for the whole cohort were 75.8%, 66.0%, 52.9% and 52.9% for 1, 2, 3 and 4 years, respectively. Patients aged <75 years had a better RFS rate compare to those older ≥75 years (60.4% vs. 38.3% respectively, p = 0.02). A total of 41 patients (53.9%) experienced immune‐related adverse events (irAEs) of any grade, and 22.3% of grade 3–5. irAEs ≥ 3 concerned 17.3% of patients aged <75 years and 33.3% for those aged ≥75 years. Thirteen patients (17.1%) had discontinued IO early due to severe irAEs after a median of 2 months (range 1–7). Median time to first recurrence from starting adjuvant programmed cell death 1 was 6.5 months (range, 1–35). Most patients recurred ON adjuvant IO (15/28 patients, 19.7%). Most of the time, first‐line therapy after melanoma recurrence was ipilimumab plus nivolumab. Objective response rate was higher for patients with recurrence within 6 months of stopping adjuvant IO (33.3%). Conclusions Real‐world outcomes of AIO for stages III/IV melanoma appeared comparable to clinical trial data. Immunotherapy appears less effective and less well tolerated in elderly patients.